(untitled) (Reflection and Critique Law Magazine, 2022)
Analyzing the process of democratization set in motion by the 1988 Constitution, guided by the concept of Democratic State of Law, the present study investigates if the new Code of Civil Procedure, sanctioned on march 16th 2015, effectively harmonizes with the Constitutional Democracy concept, allowing the real inclusion of the citizens and the implementation of the fundamental rights through the allowance of active participation on the public decision making proceeding, by the exercise of freedom to enunciate significances and the necessary attachability of such significances. So, the present study starts questioning the Code of Civil Procedure importance to the exercise and implementation of rights, considering the Explanatory Memorandum of the approved Code, entering, with greater emphasis, the examination of the court decisions standardization mechanisms proposed by the new Code, making comparative distinctions between the civil law (Roman law) and common law (case law) legal systems, as well as the precedents and standardizing application technics on which one. Proceeding to the detailed analysis of the procedures and clauses introduced by the new Code of Civil Procedure to implement the standardization of court decisions, always contrasting it with the institutive premises of the democratic processuality and the citizens freedom to enunciate significances. Concluding, ultimately, that the new Code of Civil Procedure would be able of assuring the democratic processuality if the decisions motivation duty (article 489) and the principle of no surprise (article 10) were effectively observed, as well as the principles of adversarial, defense and equality.